THE EFFECT OF COMPENSATION AND MOTIVATION ON EMPLOYEE JOB SATISFACTION DEPARTMENT OF TRANSPORTATION, SUBULUSSALAM CITY - Farida Ferine, Kiki; Suhardi, Suhardi (Universitas Efarina, 2023)
Employee job satisfaction is an employee's emotional condition where there is a match between the expected level and the real value of remuneration paid by the organization. Employee satisfaction will be reflected in the employee's feelings towards the institution in the form of a positive attitude towards his work. However, if there is no job satisfaction, employees tend to take aggressive actions, resigning from the organization. The population in this study was all employees of the Transportation Agency in Subulussalam which is 103 respondents. Data collection techniques used were questionnaires and literature study. The questionnaire will be tested for validity and reliability aspect. Furthermore, data analysis was carried out using multiple linear regression and coefficient of determination. Hypotheses testing using t test and F test. The results of this study indicate that there is a significant effect of compensation and motivation on job satisfaction in Transportation Agency in Subulussalam, both partially and simultaneously. The signifcance of compensation and motivation in job satisfaction is 59%, while the remaining 41% is explained by other variables that are not included in this research model.